ChemInform Abstract: Synthesis of Novel Imidazo[1, 2‐a]pyridin‐2‐amines from Arylamines and Nitriles via Sequential Addition and I2/KI‐Mediated Oxidative Cyclization. Issue 41 (September 2016) - Tian, Xianhai; Song, Lina; Wang, Manman; Lv, Zhigang; Wu, Jie; Yu, Wenquan; Chang, Junbiao
Abstract: A series of new imidazopyridinamines is prepared by a solvent‐free reaction of arylamines with aryl substituted acetonitriles followed by oxidative cyclization of the amidine intermediates.